La fiesta de los toros como valor cultural común o el arte de lidiar con las comunidades autónomas al amparo de la concurrencia competencial en materia de cultura - Joan Ridao Martín (Revista Vasca de Administración Pública)
The doctrine of the TC on the celebration of the bulls, although it admits the autonomic competence in the matter of culture, protection of the animals and public spectacles like qualifications that qualify to regulate the bullfighting spectacles in Catalonia and Illes Balears, maintains that the prohibition or the regulation of essential aspects thereof, aimed at preventing death or animal suffering, invades the state competence in matters of cultural heritage, prevalent in the context of the non-exclusive concurrence of state and regional competences in culture ex art. 149.2 CE, aimed at preservation of common cultural values, and that authorizes the State to intervene intensively, as the state legislator has already done, to favor a general treatment and a superordinated public action that guarantees the knowledge and survival of the bullfight as we know it modernly.